(untitled) (Iranian Journal of Kidney Diseases, 2011)
Introduction. Escherichia coli are the most frequent pathogens in acute urinary infections. They are classified based on various types of O antigen. Escherichia coli strains that cause urinary tract infections possess several genes encoding urovirulent factors. To assay the relation of virulent factors of E coli in acute urinary infections, the serotypes and virulence factor genotypes were determined. Materials and Methods. We studied 96 E coli isolates from children with acute urinary infections. Four urovirulence determinants were analyzed by DNA colony hybridization, including the genes for type 1 fimbriae (pil), P fimbriae (pap), S fimbriae (sfa), hemolysin (hly), and cytotoxic necrotizing factor 1 (cnf1). O serotypes were also determined. Results. The most frequently found virulence factor-encoding gene in the E coli strains studied was the gene for type 1 fimbriae (27.4%). The prevalence of pap, sfa, hly, and cnf1 were higher in serotypes causing pyelonephritis than cystitis. The most common type of O antigen was O1 (12.2%). There was a significant correlation between serotype and genotype in uropathogenic E coli. Conclusions. The high prevalence of O6 serotypes in children urinary tract infections and the high percentage of virulent genes in serotype O6 suggested a close relation between serotype and genotypes of uropathogen E coli.